If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
x^2-(2/3) = x-(1/2)-(1/6) // - x-(1/2)-(1/6)
x^2-x-(2/3)+1/2+1/6 = 0
x^2-x-2/3+1/2+1/6 = 0
x^2-x = 0
DELTA = (-1)^2-(0*1*4)
DELTA = 1
DELTA > 0
x = (1^(1/2)+1)/(1*2) or x = (1-1^(1/2))/(1*2)
x = 1 or x = 0
x in { 0, 1 }
| X-1/x-6 | | 2x^3+3=39 | | 9x+2=7x-6 | | -6(x-2)-2x=4-8(x+3) | | 4x^2-(-32)=-28 | | 5(z+2)=3(z+1)-1 | | 4x^2-32=-28 | | x^3+3x^2+6x+1= | | (10y-6)/(9y^2-15y) | | (9x-8)/(-6x-7) | | Y-5=x^2-6x+2 | | X^2-4x-1=-15 | | 2x^2-13=5x^2+12 | | 4x=15-(-15) | | x^3+3x^2-70x-144=0 | | 2x+50=120 | | 22=13-y | | v^2-5v-126=0 | | 2(3x+4)=19x | | 6x-2=27x+10 | | -7=-28-7 | | 12-48=3(x-4)-6 | | 3(x-4)-6=12-48 | | 2y-1/3=4y | | 12-6k=36 | | -16=0.1x-0.5x | | x^2+100=125 | | X=arcsiney | | 2x+5x=88 | | m+2+m-5=15 | | lg(x-1)=0 | | 4x^3-4x^2+x=o |